Job Satisfaction and Organizational Commitment among Constituent College Teachers in Kathmandu Metropolitan City (People's Journal of Management, 2024)
This study analyzes the correlation between job satisfaction and organizational commitment among Kathmandu T.U.-affiliated government campus faculty members. The study, which analyzed a sample size of 212 teachers, concluded that every aspect of job satisfaction positively influences organizational commitment, with colleagues having the most prominent effect. The study highlights the importance of fostering strong interpersonal relationships among colleagues to enhance job satisfaction and organizational commitment. These findings hold significant relevance for policymakers and academic institutions.